On the phylogeny, detection and behaviour of Clostridial pathogens in the soil - Palmer, Joseph Samuel (2019)
Clostridial pathogens are the aetiological agents for various human and animal diseases. Their presence in soils, manure and other organic wastes can give rise to multiple routes of infection via ingestion, inhalation or contamination of wounds, crops or silage with soil containing vegetative cells or spores. More qualitative and quantitative data are needed on the distribution, abundance and behaviour of these pathogens in agricultural soils to better manage risk.